Discussion of An Empirical Test of the Relevance of Accounting Information for Investment Decisions - Dopuch, Nicholas (Journal of Accounting Research, 1971)
Nicholas Dopuch, Discussion of An Empirical Test of the Relevance of Accounting Information for Investment Decisions, Journal of Accounting Research, Vol. 9, Empirical Research in Accounting: Selected Studies 1971 (1971), pp. 32-40